500 Activities for the Primary Classroom - Read, Carol (Macmillan Education, 2015)
Aimed at teachers of children between the ages of 3-12, this is a lively, varied compendium of ideas and classroom activities. Key features include: wide-ranging resource of activities which are easy to set up and do not require a lot of additional materials; and up-to-date approach that covers current approaches in teaching children including content-based learning. It is ideal for all primary-focused teachers, including those on teacher training courses such as the Cambridge CELTYL. It is designed to be flexible to supplement a wide range of syllabus-types (story-based, grammatical, etc.).